Feasibility of power-type strength training for middle aged men and women: self perception, musculoskeletal symptoms, and injury rates - Surakka, J.; Aunola, S.; Nordblad , T.; Karppi, S. L.; Alanen, E. (British Journal of Sports Medicine, 2003)
Objectives: To examine the feasibility of a power-type strength training programme for middle aged men and women, the impact of the training programme on perceived health and fitness and on knee and low back symptoms, and the rate of exercise induced injuries.